MethFinder - A software package for prediction of human tissue-specific methylation status of CpG islands - James, Priyanka (Biomedical Informatics, 2013)
DNA methylation, the highly studied epigenetic mechanism which is involved in the regulatory events of various cellular processes like chromatin structure modifications, chromosomal inactivation, gene expressional patterns, embriyonic developments and transcriptional modification etc. Various high throughput techniques evolved for direct detection of methylation actions as well as information across the entire region. However, despite high throughput technological advances in experimental field, the development of software tools that has been dedicated to the prediction of epigenetic information from specific genome sequences is warranted. To this end we developed a tissue specific classifier MethFinder based on the frequency of novel sequence patterns across nine human tissues that was capable of discriminating methylation prone and methylation resistant CpG islands with an overall accuracy of 93%. AVAILABILITY: MethFinder is freely available at www.rgcb.res.in/methfinder